Creativity Profile Of Accounting Teachers In The Era Of Independent Learning - Mufti Zahroh Latifah Auladana; Sri Sumaryati (FKIP, Universitas Palangka Raya, 2024)
This research aims to (1) obtain information regarding teacher creativity in implementing the independent curriculum, (2) determine the obstacles that arise in achieving creative teachers. This research is descriptive qualitative research using interviews and observation techniques, then the data is processed using Miles and Huberman data analysis. Based on the research results, it can be concluded that creativity in preparing teaching modules and teaching materials is grouped into four dimensions, namely personal dimensions, process dimensions, product dimensions and press dimensions. The personal dimension of creativity in preparing teaching modules can be seen from the application of differentiated learning, the application of learning methods, and the elements of teaching modules. The dimensions of the creativity process in preparing teaching modules can be seen from the survey of student needs and understanding of learning outcomes, learning objectives and the flow of learning objectives. The product dimension of creativity in preparing teaching modules can be seen from the appearance of the teaching module and the content of the teaching module. In the press dimension, creativity in preparing teaching modules can be seen from the recognition and responses of other people. Meanwhile, the personal dimension of creativity in preparing teaching materials can be seen from the diversity of teaching materials and learning media as well as the depth of materials and assessments. The dimensions of the creativity process in preparing teaching materials can be seen from understanding the teaching materials. In the product dimension, creativity in preparing teaching materials can be seen from the resulting teaching materials. In the press dimension, creativity in preparing teaching materials can be seen from the recognition and responses of other people. Barriers that are often experienced include self-motivation, time management, and mastery of information technology.